Incidence of Post Instrumentation Pain Following Endodontic Treatment Among Patients Attending College of Dentistry-Hawler Medical University. - Intesar Saadallah Toma; Hussein Jamal Hashim; Muhammed Amir Salahadin; Muhammed Dana Razaq (Erbil Dental Journal)
Background and objective: The background of this study revolves around endodontic treatment, which is a therapeutic approach involving the chemical and mechanical disinfection of root canals, followed by the establishment of a secure three-dimensional seal. The primary objective of this research is to investigate and understand the underlying factors that contribute to flare up experienced by patients undergoing endodontic treatment.